Adrenergic receptor signaling regulates the CD40-receptor mediated anti-tumor immunity - Singh, Akansha; Ranjan, Ashish (Frontiers in Immunology, 2023)
Abstract Anti-CD40 agonistic antibody (CD40), an activator of dendritic cells (DC) can enhance antigen presentation and activate cytotoxic T-cells against poorly immunogenic tumors. However, cancer immunotherapy trials also suggest that CD40 is only moderately effective in patients, falling short of achieving clinical success. Identifying factors that decrease CD40 immune-stimulating effects can aid the translation of this agent to clinical reality. Here, we reveal that -adrenergic signaling on naïve DCs directly interferes with CD40 efficacy in immunologically cold head and neck tumor model. We discovered that -2 adrenergic receptor (2AR) activation reengineers CD40 signaling in DCs by directly inhibiting the phosphorylation of IB and indirectly by upregulating levels of phosphorylated-cAMP response element-binding protein (pCREB). Importantly, the addition of propranolol, a pan -Blocker reprograms the CD40 pathways, resulting in superior tumor regression. This is also accompanied by higher cytotoxic T-cell infiltration and lower regulatory T-cell burden in tumors compared to respective monotherapies. Thus, our study highlights an important mechanistic link between stress-induced 2AR signaling and reduced CD40 efficacy in cold tumors, providing a new combinatorial approach to improve clinical outcomes in patients.